Pelatihan Yoga untuk Mengatasi Nyeri Haid pada Remaja Putri di Kelurahan Langensari RT 02 RW 05 - Shintya Putriningrum; Vistra Veftisia; Ginaya Dinda Putri (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2022)
Dysmenorrhea or menstrual pain is pain or cramping in the lower abdomen that appears before or during menstruation. Dysmenorrhea can be mild, but it can also be so severe that it interferes with daily activities. The results of the study on data collection showed that in RT 02 RW 05 in the Langensari village, young women had problems, namely the lack of adolescent knowledge about menstrual pain or dysmenorrhea and its handling by pressing the stomach. This lack of knowledge is because young women have not received information about dysmenorrhea and its treatment. In this regard, the activity was carried out in 3 stages. First is preparation by preparing all needs for counseling events such as the media used by PPT, yoga exercise demonstration materials and yoga gymnastics mats, as well as counseling places, Second is the implementation with the arrangement of events that will be carried out starting from pre-test and post-test preparation, delivery of materials, demonstration of yoga exercise and the third is the evaluation of the counseling event or summary of the conclusions of this youth counseling. The instrument used is a questionnaire. Before being given counseling, the average value of pre-test knowledge of adolescent girls about dealing with menstrual pain was 58.69. After being given counseling and training in yoga exercise to overcome menstrual pain the average post-test score of adolescent girls was 75.00. This shows that there is an increase in the knowledge of young women after being given counseling on dysmenorrhea material and yoga exercise training. AbstrakDismenore atau nyeri haid adalah nyeri atau kram di perut bagian bawah yang muncul sebelum atau saat menstruasi. Dismenore dapat bersifat ringan, tetapi juga bisa parah sehingga mengganggu aktivitas sehari-hari. Hasil pengkajian pada pengumpulan data didapatkan hasil di RT 02 RW 05 di kelurahan Langensari yaitu remaja putri memiliki masalah yaitu kurangnya pengetahuan remaja tentang nyeri menstrusasi atau disminorea dan penanganannya dengan menekan perut. Pengetahuan yang kurang ini disebabkan karena remaja putri belum mendapatkan informasi mengenai dismenorea dan penanganannya. Berkaitan dengan masalah tersebut, kegiatan dilaksanakan dalam 3 tahap. Pertama adalah Persiapan dengan menyiapkan segala keperluan untuk acara penyuluhan seperti media yang digunakan PPT, materi demonstrasi senam yoga dan matras senam yoga, serta tempat penyuluhan, kedua adalah pelaksanaan dengan susunan acara yang akan dilakukan mulai dari pengisian pre test dan post tes, penyampaian materi, demonstrasi senam yoga dan yang ketiga adalah evaluasi dari acara penyuluhan atau ringkasan kesimpulan penyuluhan remaja ini. Instrumen yang digunakan adalah kuesioner. Sebelum diberikan penyuluhan rata – rata nilai pre test pengetahuan remaja putri tentang mengatasi nyeri haid adalah 58,69, Setelah diberikan penyuluhan dan pelatihan senam yoga untuk mengatasi nyeri haid rata-rata nilai post test remaja putri adalah 75.00. Hal ini menunjukan bahwa terdapat peningkatan pengetahuan remaja putri setelah diberi penyuluhan materi dismenorea dan pelatihan senam yoga.